Respiratory-induced hemodynamic changes measured by whole-body multichannel impedance plethysmography - Langer, P; Jurák, P; Vondra, V; Halámek, J; Mešťaník, M; Tonhajzerová, I; Viščor, I; Soukup, L; Matejkova, M; Závodná, E; Leinveber, P (Physiological research, 2018)
The cardiovascular system is described by parameters including blood flow, blood distribution, blood pressure, heart rate and pulse wave velocity. Dynamic changes and mutual interactions of these parameters are important for understanding the physiological mechanisms in the cardiovascular system. The main objective of this study is to introduce a new technique based on parallel continuous bioimpedance measurements on different parts of the body along with continuous blood pressure, ECG and heart sound measurement during deep and spontaneous breathing to describe interactions of cardiovascular parameters. Our analysis of 30 healthy young adults shows surprisingly strong deep-breathing linkage of blood distribution in the legs, arms, neck and thorax. We also show that pulse wave velocity is affected by deep breathing differently in the abdominal aorta and extremities. Spontaneous breathing does not induce significant changes in cardiovascular parameters.
Keywords: dospělí; Hemodynamics; mladý dospělý; hemodynamika; Respiratory Mechanics; pletyzmografie celotělová; lidé; analýza pulzové vlny; Female; mužské pohlaví; Pulse Wave Analysis; Young Adult; Male; Plethysmography, Whole Body; mechanika dýchání; Adult; ženské pohlaví; Humans